Cultural Empowerment and Economic Upturn: Unveiling Bojonegoro's Wayang Thengul Tourism - Wintari Wintari; Dwiningtyas Padmaningrum; Haryani Saptaningtyas (Indonesian Journal of Cultural and Community Development, 2023)
This research delves into the cultural and economic potential of Bojonegoro regency in East Java, focusing on the unique three-dimensional puppetry tradition known as Wayang Thengul. Situated in Kedungkrambil hamlet, Sumberjo Village, Margomulyo sub-district, this study employs qualitative descriptive methods including in-depth interviews, observation, and documentation to explore the empowerment of local communities through the development of cultural tourism. By harnessing the heritage of Wayang Thengul and leveraging geographical advantages, the project "Kampoeng Thengul" was initiated to invigorate the economy. Results demonstrate that community engagement in tourism activities and planning plays a pivotal role in stimulating economic growth. This investigation offers valuable insights into community-driven cultural tourism initiatives and their significant contributions to local economies. Highlight: Unveiling Cultural Riches: This study explores the distinctive Wayang Thengul puppetry tradition as a cultural and economic asset in Bojonegoro regency, East Java. Community-Driven Empowerment: Through qualitative methods, the research highlights the vital role of local community involvement in the development of "Kampoeng Thengul" cultural tourism project. Economic Catalyst: Findings emphasize the significant contribution of community engagement in cultural tourism to stimulate robust economic growth in the region. Keyword: Cultural Potential, Economic Development, Wayang Thengul, Community Empowerment, Cultural Tourism